2016
DOI: 10.1186/s12896-016-0270-0
|View full text |Cite
|
Sign up to set email alerts
|

New strategy for testing efficacy of immunotherapeutic compounds for diabetes in vitro

Abstract: BackgroundThe valuable role of immunotherapy in treating autoimmune diseases is increasingly recognized by those involved in the research and clinical application of new biopharmaceuticals products. However, many aspects related to the mechanisms of immune-modulated therapies remain to be elucidated in order to explore fully the emerging opportunities. The non-obese diabetic NOD mouse develops insulin-dependent diabetes mellitus spontaneously as a consequence of an autoimmune process in the presence of pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…HSP70 plays an important role in antigen presentation, activation of macrophages and lymphocytes, as well as activation and maturation of dendritic cells [ 7 ]. Studies have shown that HSP70 has the ability to transform Th17 cells immune response mode into Treg cells immune response mode [ 18 ]. However, whether HSP70 is related to the ratio of Treg/Th17 in PCOS patients has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…HSP70 plays an important role in antigen presentation, activation of macrophages and lymphocytes, as well as activation and maturation of dendritic cells [ 7 ]. Studies have shown that HSP70 has the ability to transform Th17 cells immune response mode into Treg cells immune response mode [ 18 ]. However, whether HSP70 is related to the ratio of Treg/Th17 in PCOS patients has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The immunotherapeutic capacity of DNAhsp65 to control infectious diseases, autoimmune diseases, allergy, and tumors, which have significant differences in their immunopathology, is associated with a number of factors with distinct immunomodulatory capabilities inherent to the structure and/or composition of DNAhsp65 (4). The main factors that stand out include the presence of an HSP that has significant activities in the recognition, intracellular trafficking, antigen presentation (peptide), and interaction with receptors and signaling for activation of the innate and the adaptive immune system (17)(18)(19)(20)(21); the ability of HSPs to bind and form complexes with peptides derived from tumor or infected cells and to induce innate and/or adaptive immune response against chaperoned peptides (5,9,14); a DNA vaccine that by itself releases endogenous antigens and/or immunomodulators to stimulate innate and adaptive (cellular and humoral) immunity (9,24); the presence of immunostimulatory DNA sequences containing CpG motifs in the plasmid DNA backbone that is considered to be an important adjuvant for generating the innate and Th1 immune response (17,(78)(79)(80); the double-stranded structure of the DNA plasmid that is also thought to be an immune stimulant through non-TLR mechanisms (acting on the TBK1-STING pathway through cytosolic receptors), resulting in the generation of Type-1 interferon, which then act as an adjuvant for the generation of immune responses against the antigen(s) encoded by the plasmid DNA vaccine (87,88); the capacity for activation and regulation of adaptive immune response among Th1, Th2, Th17, Treg, and γδT pattern of lymphocytes (38,45,(64)(65)(66)71); and the properties of formulations or particulate delivery system and/or adjuvants to stimulate innate and adaptive immunity (27,28,54).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the insulitis score was decreased as a result of reduced T-CD4 + and T-CD8 + cell infiltration and Treg-IL-10 + activation ( 64 , 65 ). Moreover, when cocultures of APCs and NOD mouse T cells were incubated in the presence of DNAhsp65, Hsp65, or Hsp70 mycobacterial HSPs, the response pattern was altered from Th17 to Treg cells, showing increased IL-10 secretion and reduced IL-6, IFN-γ, and IL-17 cytokine production ( 66 ). The prime-boost strategy involving the BCG and DNAhsp565 vaccines (BCG/DNAhsp65) used as a new treatment approach reestablished blood glucose levels, reduced the inflammatory process in pancreatic islets, and promoted increased weight only in NOD mice.…”
Section: Dnahsp65 In Autoimmune Diseases Modulationmentioning
confidence: 99%
“…Since the discovery that DNA-hsp65 can have immunomodulatory and/or immunoregulatory action against TB several other works have been done by our group with other infectious diseases, autoimmune diseases, allergy, and tumors. Thus, it was demonstrated that DNA-hsp65 presents broad immunotherapeutic properties for leishmaniasis [12], schistosomiasis [9,11], paracoccidioidomycosis [13,14], chromoblastomycosis [15], helminths [10]; autoimmune diseases such as diabetes [16][17][18][19], arthritis [20,21], encephalomyelitis [22][23][24], and atherosclerosis [25], allergic diseases such as asthma and atopic dermatitis [26][27][28] and tumors in experimental models of mice and in phase I/II clinical trial in humans [29,30]. Thus, DNA-hsp65 actively participates in the activation of innate immunity, acting as an endogenous adjuvant and playing a fundamental role in the activation and control of adaptive immunity [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%